Architecture of service-oriented data analysis system - Baoyou WANG; Cong WU; Jing QIAN; Xiaoying TAO (Dianxin kexue)
In the era of data technology,the higher requirements of telecom operators,such as business innovation and strong operation supporting,are being placed on data analysis system.Firstly,the requirement and challenge of the rising data analysis and the enhancing data value were expounded.Then,in order to realize open architecture and flexible operation support,the logical framework and technology architecture of the service-oriented data analysis system,as well as the data governance and the data security management were proposed.Finally,the service scenarios and the business value of the platform were introduced by an example.